Statistical analysis by means of the program SPSS - Lisimaco, V. C.; Justo, A. A. (International Journal of Computer Science in Sport, 2002)
Statistical analysis by means of the program SPSS of the effects of a program of training on the development of the physical condition based on the physical performance.